A novel shift control concept for multi-speed electric vehicles. (November 2018) - Mo, Wenwei; Walker, Paul D.; Fang, Yuhong; Wu, Jinglai; Ruan, Jiageng; Zhang, Nong
Highlights: A novel synchronizer named Harpoon-Shift for electric vehicles. Harpoon-Shift uses torque springs rather than friction clutch for speed synchronization. Only a small thrust load is required for engagement of Harpoon-Shift. It simplifies control strategy of gear shifting and the actuation process is simpler. Rotating inertia, speed difference, and spring stiffness affect the Harpoon-shift dynamic performance. Abstract: This paper proposes a novel synchronizer 'Harpoon-Shift' aiming at improving the comfort and efficiency of gearbox, meanwhile, simplifying the shifting control strategy for multi-speed electric vehicles. It will overcome one of the biggest shortcomings of traditional synchronizer system with frictional cone clutch. Experiment is established to investigate the torque and speed responses during the engagement of gears pairs. Then, based on previous testing results, the relationship of the peak torque and minimum speed difference to implement gear shifting with various spring coefficients is investigated. In addition, a mathematical model of the Harpoon-Shift system is developed to simulate the engagement process. The simulation results of system transient responses are validated against the data measured on testing rig. The model is then improved to study the impact of the rotating inertia, speed and speed difference on the torsional vibration and required time of engagement. Both of the simulation and experimental results show the significant improvement of proposed synchronizer to conventional cone clutch synchronizer.